The development of wheat/Thinopyrum elongatum lines produced via a whole genome shotgun approach and characterisation via cytogenetics and molecular marker analysis - Baker, Lauren (2018)
Providing a sustainable supply of wheat for a growing global population, whilst managing additional challenges such as climate change and land availability, is a huge challenge for breeders. The two hybridisation events that occurred during wheat’s evolution and the subsequent genetic bottleneck, combined with over a century of intensive selection has severely limited the genetic diversity available in the wheat gene pool, directly limiting any improvements breeders can make to increase yield to meet future demand. Thinopyrum elongatum 401007 is a wild relative of wheat known to contain a plethora of genes beneficial for abiotic and biotic stress tolerance. Genes for leaf rust resistance (Lr19, Lr24, Lr29), stem rust resistance (Sr24, Sr25, Sr43) and powdery mildew resistance (Pm51) have already been exploited. Therefore, Th. elongatum 401007 (2n = 10x = 70 (+2)) is being used in this programme to develop chromosome introgression lines in bread wheat, with the aim to increase the genetic diversity available for future breeders. The action of wheat ph1/ph1 deletion mutants is exploited to enable initial wide interspecies crosses. The Nottingham BBSRC WRC shotgun breeding programme has successfully generated over 8,000 crossed seed and over 55,000 self-fertilised seed from the wheat/Th. elongatum breeding pipeline and has reached the BC5 and BC5F1 generation. From these lines, GISH has identified 143 introgressions from 327 back-crossed lines. Multi – colour GISH has also shown a closer relationship between the B and A genomes of wheat with the E genome of Th. elongatum than previously known. Mc-GISH was also used to investigate the genomic constitution of Th. elongatum 401007. In total, 263 Affymetrix SNP markers have been validated and used to identify 202 introgressions from 352 back-crossed lines. They have also been used to produce a putative linkage map of the E genome. A previously unknown inversion of chromosome 7E in comparison to 7D was discovered and the 4/5 translocation known to be present in wheat was shown to be absent in the genome of Th. elongatum. Development and initial testing of KASP markers is shown and ongoing.